Effect of protein supplementation on tropical grass hay utilization bybeef steers drinking saline water - López, A. (2014)
An experiment was conducted to assess the impact of increasing levels of supplemental soybean meal (SBM; 45.7% CP) in cattle consuming tropical grass hay (Panicum maximum cultivar Gatton; 7.0% CP and 81.8% NDF) and drinking low salt water (LS) or high salt water (HS). Six ruminally fistulated beef steers (BW = 375 ± 43 kg) were used in a 6-treatment, 4-period crossover experiment. Treatments were arranged as a 2 × 3 factorial, with 2 levels salt in the water (LS and HS: 786 and 6,473 mg/kg of total dissolved solids [TDS], respectively) and 3 levels of SBM (0, 0.2, and 0.4% BW/d). After 15 d of adaptation to treatments, periods consisted of 5 d for intake and digestibility determination, 1 d for monitoring ruminal fermentation, 1 d for ruminal evacuation, and 1 d for blood sampling. Supplemental SBM × water quality interactions were significant (P < 0.05) for most measures of intake, except for total tract digestible OM intake (P = 0.38) and total tract digestible NDF intake (TTDNDFI; P = 0.32). At greater levels of SBM, forage OM intake, NDF intake, and water intake seemed to reach a plateau in LS while this was not observed in HS. Total tract digestible OM intake increased linearly (P = 0.01) and TTDNDFI tended to increase (P = 0.09) in response to increased SBM. Digestibility of OM and NDF were not affected by treatment (P > 0.21). Passage rate of acid detergent insoluble ash linearly increased (P < 0.01) in response to SBM, although it was not affected by water quality (P = 0.98). Total VFA concentrations and ruminal pH were not affected (P > 0.60 and P > 0.31, respectively) by treatment. Ruminal ammonia N levels were linearly increased by SBM supplementation (P < 0.01) but were not affected by water quality (P = 0.25). However, ruminal ammonia tended (P = 0.09) to be greater in HS at 0.2% of SBM supplementation. No interaction was observed for plasma urea N (PUN; P = 0.20). Plasma urea N was affected by SBM supplementation (P = 0.05) and water quality (P < 0.01). However, PUN did not differ for 0.4% SBM supplementation (P = 0.30) either at LS or HS treatments. In conclusion, a high level of SBM supplementation (0.4% BW) counteracted the detrimental effect of high TDS in drinking water on low-quality forage consumption by cattle.